On The Uniqueness of Meromorphic Functions Sharing Three-Point Sets IM - Kongo, Takahiro; Shirosaki, Manabu (IndoMS, 2020)
We show that if two meromorphic functions on the complex plane shring some three-point sets IM, then they are identical under some conditions.